Actions of female sex workers faced with condom failure during penetration sexual encounters with clients in Cape Town - Mukumbang, Ferdinand Chemungha (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.